Ramucirumab plus docetaxel versus placebo plus docetaxel in patients with locally advanced or metastatic urothelial carcinoma after platinum-based therapy (RANGE): a randomised, double-blind, phase 3 trial. Issue 10109 (18th November 2017) - Petrylak, Daniel P; de Wit, Ronald; Chi, Kim N; Drakaki, Alexandra; Sternberg, Cora N; Nishiyama, Hiroyuki; Castellano, Daniel; Hussain, Syed; Fléchon, Aude; Bamias, Aristotelis; Yu, Evan Y; van der Heijden, Michiel S; et al.
Summary: Background: Few treatments with a distinct mechanism of action are available for patients with platinum-refractory advanced or metastatic urothelial carcinoma. We assessed the efficacy and safety of treatment with docetaxel plus either ramucirumab—a human IgG1 VEGFR-2 antagonist—or placebo in this patient population. Methods: We did a randomised, double-blind, phase 3 trial in patients with advanced or metastatic urothelial carcinoma who progressed during or after platinum-based chemotherapy. Patients were enrolled from 124 sites in 23 countries. Previous treatment with one immune-checkpoint inhibitor was permitted. Patients were randomised (1:1) using an interactive web response system to receive intravenous docetaxel 75 mg/m 2 plus either intravenous ramucirumab 10 mg/kg or matching placebo on day 1 of repeating 21-day cycles, until disease progression or other discontinuation criteria were met. The primary endpoint was investigator-assessed progression-free survival, analysed by intention-to-treat in the first 437 randomised patients. This study is registered withClinicalTrials.gov, numberNCT02426125 . Findings: Between July, 2015, and April, 2017, 530 patients were randomly allocated either ramucirumab plus docetaxel (n=263) or placebo plus docetaxel (n=267). Progression-free survival was prolonged significantly in patients allocated ramucirumab plus docetaxel versus placebo plus docetaxel (median 4·07 months [95% CI 2·96–4·47] vs 2·76 months [2·60–2·96]; hazard ratio [HR] 0·757, 95% CI 0·607–0·943; p=0·0118). A blinded independent central analysis was consistent with these results. An objective response was achieved by 53 (24·5%, 95% CI 18·8–30·3) of 216 patients allocated ramucirumab and 31 (14·0%, 9·4–18·6) of 221 assigned placebo. The most frequently reported treatment-emergent adverse events, regardless of causality, in either treatment group (any grade) were fatigue, alopecia, diarrhoea, decreased appetite, and nausea. These events occurred predominantly at grade 1–2 severity. The frequency of grade 3 or worse adverse events was similar for patients allocated ramucirumab and placebo (156 [60%] of 258 vs 163 [62%] of 265 had an adverse event), with no unexpected toxic effects. 63 (24%) of 258 patients allocated ramucirumab and 54 (20%) of 265 assigned placebo had a serious adverse event that was judged by the investigator to be related to treatment. 38 (15%) of 258 patients allocated ramucirumab and 43 (16%) of 265 assigned placebo died on treatment or within 30 days of discontinuation, of which eight (3%) and five (2%) deaths were deemed related to treatment by the investigator. Sepsis was the most common adverse event leading to death on treatment (four [2%] vs none [0%]). One fatal event of neutropenic sepsis was reported in a patient allocated ramucirumab. Interpretation: To the best of our knowledge, ramucirumab plus docetaxel is the first regimen in a phase 3 study to show superior progression-free survival over chemotherapy in patients with platinum-refractory advanced urothelial carcinoma. These data validate inhibition of VEGFR-2 signalling as a potential new therapeutic treatment option for patients with urothelial carcinoma. Funding: Eli Lilly and Company.